Analysis of Premarital Sex Factor Through Self-Control in Teenagers At Senior High School / Equals in Sarolangun Regency - Salviana, Eka Asvista; Made Sudana, I; Hary Cahyati, Widya (Public Health Perspective Journal, 2020)
Premarital sexual cases in adolescents can be caused due to various conditions and several factors. Data from the National Population and Family Planning Board (BKKBN) in 2017 shows that in Jambi Province there were cases of adolescents aged 15-19 who gave birth or pregnant with their first child with a percentage of 10.9%. This study aimed to analyze the effect of knowledge and information media on the incidence of premarital sex in adolescents in Senior High School/Equals at Sarolangun Regency, Jambi Province. The type of research was an observational analytic study with a cross sectional design. The research sample was 371 adolescents. The analysis used in this research was Path Analysis. The results showed that knowledge had a negative and significant effect directly on the incidence of premarital sex, and there was a positive and significant effect directly from the information media on the incidence of premarital sex with a significant value for information media of 0.042 <0.05. Furthermore, on the incidence of premarital sex through self-control, it was found that knowledge had a negative and significant effect on premarital sex through self-control, and the results showed that information media had a positive and significant effect on the incidence of premarital sex through self-control.